Creative ageing and the arts of care : reframing active ageing - Brooke, Elizabeth, active 2022 (Emerald Publishing Limited, 2022)
Creative Ageing and the Arts of Care makes a case for cultural participation by older adults to enhance the quality of their lives. Building on concepts of adult human development and empowerment, Elizabeth Brooke reframes 'active ageing' to include forms of creative expression and cultural participation crucial to transforming later stages of the life course. Focusing on the micro-level of the experiences of older adults in visual arts, dance, theatre and music, the book showcases multi-perspective case studies compiled from community-based initiatives and care settings carried out in the United States, United Kingdom, Ireland, and Australia to explain creative ageing in practice. Through the analysis of arts forms embedded in theoretical sociological frameworks and the lens of cultural gerontology, the case studies explore and develop theoretical insights about older adults' experiences of artmaking which also contest ageism. The case studies interrelate meso-level interactional processes entailed in art-making and macro-level structural contexts. Drawing out success factors, the author articulates a transferable policy framework and practical recommendations for a multi-level model of creative ageing. Breaking fresh ground by proposing a new conceptual and practical framework promoting 'creative ageing', Elizabeth Brooke ultimately argues that 'active ageing' must be reframed to include cultural participation as an integral domain at the crux of wellbeing. Ultimately, the book demonstrates how quality of life and quality of care, including self-care, coincide by enabling adults to flourish creatively as they age.